PENGARUH PENGGUNAAN QRIS DAN CASHLESS LIFESTYLE TERHADAP FREKUENSI TRANSAKSI PENGGUNA PADA GENERASI Z DI KECAMATAN MARON - Galang Khairan Iqbal Eudriana; Muh Hamzah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of the use of the Quick Response Code Indonesian Standard (QRIS) and a cashless lifestyle on the transaction frequency of Generation Z users in Maron District. The rapid development of digital payment technology has transformed consumer behavior, particularly among Generation Z, which tends to adopt digital financial innovations more readily. This study employed a quantitative approach using a survey method. The research population consisted of Generation Z individuals residing in Maron District who had used QRIS as a payment method. The sample was selected using purposive sampling, with respondents aged 17–27 years who actively conducted transactions using QRIS. Data were collected through a questionnaire based on a Likert scale and analyzed using multiple linear regression to examine the individual and simultaneous effects of the independent variables. The results indicate that the use of QRIS has a positive and significant effect on transaction frequency, as it provides convenience, speed, security, and efficiency in payment transactions. Furthermore, a cashless lifestyle also has a positive and significant effect on transaction frequency, indicating that the greater the tendency of individuals to adopt a cashless lifestyle, the higher their transaction frequency. Simultaneously, the use of QRIS and a cashless lifestyle significantly influence the transaction frequency of Generation Z users in Maron District. These findings are expected to provide valuable insights for digital payment service providers and policymakers in promoting the adoption of cashless payment systems within the community.